Modified Polystyrene Waste as Cation Exchange Material and Its Characterization - Nendo, Felicia Febyola; Sutanto, Teja Dwi; Banon, Charles; Angasa, Eka; Gustian, Irfan (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2026)
Modification of polystyrene (PS) waste into sulfonated polystyrene (PSS) as cation exchange material and its characterization has been carried out, the polystyrene waste used is styrofoam from air conditioner packaging. Modification is carried out through the sulfonation process of styrofoam using acetyl sulfate as a sulfonating agent in tetrahydrofuran (THF) solution. Sulfonation is carried out at a temperature of 40 °C for 3.5 hours under nitrogen gas flow. The modified product is then characterized using FTIR, SEM, and testing the degree of sulfonation, water absorption capacity, and cation exchange capacity (CEC). The results show that modification has occurred in the presence of a sulfonate group (–SO₃H) which is characterized by the appearance of characteristic peaks of 1033 cm⁻¹, 1162 cm⁻¹ and 3329 cm⁻¹ in the FTIR spectrum and SEM results show that the PS structure which is not rough and becomes a rougher and non-uniform structure after sulfonation. The degree of sulfonation obtained reached 58%, the maximum water absorption achieved was 39% after soaking for 72 hours, and the highest measured cation exchange capacity was 1.87 meq/g in 1.5 N NaCl solution. These results indicate that styrofoam waste has the potential to be used as a basic material for efficient and environmentally friendly cation exchange resins.Keywords: Polystyrene, Sulfonation, Acetyl sulfate, Cation exchange capacity, Activation energy